PENYELESAIAN PERSELISIHAN BISNIS WARALABA (FRANCHISE): STUDI KASUS SEAFOOD MAS BR CAB. II WILAYAH KOTA DEPOK: Franchise Business Dispute Resolution: Case Study of Seafood Mas BR Cab. II Depok City Area - Sartika, Indah Yuli (Jurnal Globalisasi Hukum., 2024)
Franchising is becoming a phenomenal business model in global business in various industrial sectors, such as food, retail, and services. By utilizing brands and concepts that have proven successful and obtaining operational and management support from franchisees in practice, this business model is not free from various risks and problems. One of the problems faced is the potential for the parties to default because it is not in accordance with the agreed results. This paper aims to identify and analyze dispute resolution if there is a dispute on both franchise parties. The study's findings revealed that, beyond the initial conclusions, the Civil Code there are several rules underlying legal protection related to the franchise business, but the author suggests making preventive efforts by prioritizing out-of-court settlements such as mediation with deliberation to reach consensus.